Image fusion in X-ray differential phase-contrast imaging - Haas, Wilhelm; Polyanskaya, Maria; Bayer, Florian; Gödel, Karl Christoph; Hofmann, Hannes; Rieger, Jens; Ritter, André; Weber, Thomas; Wucherer, Lukas; Durst, Jürgen; Michel, Thilo; Anton, Gisela; et al. (Medical Imaging 2012: Image Processing, 2012)
Phase-contrast imaging is a novel modality in the field of medical X-ray imaging. The pioneer method is the grating-based interferometry which has no special requirements to the X-ray source and object size. Furthermore, it provides three different types of information of an investigated object simultaneously - absorption, differential phase-contrast and dark-field images. Differential phase-contrast and dark-field images represent a completely new information which has not yet been investigated and studied in context of medical imaging. In order to introduce phase-contrast imaging as a new modality into medical environment the resulting information about the object has to be correctly interpreted. The three output images reflect different properties of the same object the main challenge is to combine and visualize these data in such a way that it diminish the information explosion and reduce the complexity of its interpretation. This paper presents an intuitive image fusion approach which allows to operate with grating-based phase-contrast images. It combines information of the three different images and provides a single image. The approach is implemented in a fusion framework which is aimed to support physicians in study and analysis. The framework provides the user with an intuitive graphical user interface allowing to control the fusion process. The example given in this work shows the functionality of the proposed method and the great potential of phase-contrast imaging in medical practice. © 2012 SPIE.